'Wind‐up' in Parkinson's disease: A functional magnetic resonance imaging study. (12th March 2015) - Aschermann, Z.; Nagy, F.; Perlaki, G.; Janszky, J.; Schwarcz, A.; Kovacs, N.; Bogner, P.; Komoly, S.; Orsi, G.
Abstract Background Parkinson's disease (PD) is a neurodegenerative disorder mainly marked by selective degeneration of dopaminergic neurons that leads to disabling motor and cognitive impairment. This condition is less widely appreciated as a disease associated with a substantial variety of pain syndromes, although the prevalence of pain is relatively high. Repeated painful stimulation of peripheral nerves can cause pain 'wind‐up' if the frequency of the stimulation is adequate and specifically stimulates the afferent C‐fibres. We presumed that in case of PD, pain or pain severeness might be frequently caused by the aggravation of the 'wind‐up' phenomenon due to any central or peripheral lesions or functional alterations. Methods To test for this hypothesis, we compared three groups (patients with left‐ and right‐dominant PD and control subjects) using functional magnetic resonance imaging and thermally induced pain. Results Patient showed higher average 'wind‐up' scores, compared to the healthy subjects, with lower values on the more affected sides compared to the less affected ones. In group level comparisons, patients had higher activation during 'wind‐up' compared to control subjects in two main areas; these were the posterior division of cingulate gyrus and the precuneus cortex. In case of patients, further analyses showed that applied heat pain on the less affected side elicited higher activation in the supramarginal and postcentral gyri. Conclusions These differences may arise from the deficiency in the efferent information, as well as the alterations in the central processing. It is highly likely that both processes contribute to this phenomenon simultaneously.